Ekonomi Kerakyatan: Dari, Oleh Dan Untuk Nasionalisme - wedi prasetyo (Universitas Islam Balitar, 2016)
Study this article aims to emphasize the importance ofdemocratic economy in an effort to confront global trade towardsnationalism. This achievement makes the spirit of awakening thepeople's welfare. The results of this study can increase the ability oflocal potential (cluster) through the development of anentrepreneurial spirit, koperasi and BUMDesa. In addition, also forthe government of the City and or district can develop a clusterstrategy in implementing the Economic Policy Net (NET). This kindof policy in order to develop the potential of the area was able to seeand develop superior power and competitiveness of products. Theresult is a formidable foster economic actors for culture and socialcapital at once in turn also